'As I Drifted on a River I Could Not Control': The Unintended Ordoliberal Consequences of the Eurozone Crisis*. (13th April 2015) - Nedergaard, Peter; Snaith, Holly
Abstract Germany has a long history of institutionalized ordoliberalism. While these ideas may be implemented almost unreflexively within Germany, its status of 'reluctant hegemon' within the European Union has led to purposive uploading of many of these ideas to other Member States. In this article, we first define what these ordoliberal actions consist of, before tracing their evolution within Germany and the EU. Our intention is to detail how acting within ordoliberal tenets has led to some rather messy and unpredictable results for Germany and other EU Member States alike – a state particularly emphasized by the crisis. In so doing, we (re)invoke Robert Merton's treatment of unintended consequences. In particular, we are concerned with Germany's increased role in enforcing fiscal order in the EU, counter to our interviewees' (drawn from the Ministry of Finance and the Ministry of Foreign Affairs) express intentions to retain Germany's political distance.